The Alternative Use of Straw - Mészáros, Szilvia (International Journal of Engineering and Management Sciences, 2017)
The problem addressed in this work is to examine the feasibility of using straw in innovative and alternative ways, focusing on aspects of cost sensitivity in subject areas of building investment and energy compsumption. I analysed the energy efficient performance of a straw bale building and compared that with those of a conventional construction, a newly-constracted building and a passive house. In my study I assessed the figures of costs of emboided energy, primary energy consumption and carbon dioxide emission. I made calculations in terms of energy costs for a lifespan of 50 years. Considering that straw-bale construction uses an excellent and sustainable insulation material, its energy use is by 25.38% less than that of conventional construction.